A (in) visibilidade da escola: implicações das avaliações externas no contexto escolar - Ivan Amaro (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
In Brazil, since the 1990s, the policies of large-scale assessments follow world politics and settled with the main objective of verifying the quality of education. After nearly 20 years, are visible the impact of these policies in public schools. The disclosure promotes a results-based visibility and, concomitantly, an invisibility of schools. We discuss the effects that these assessments have promoted the work of teachers and schools, focusing on tensions generated from the national examinations for which the school is basic. We try to also point out possibilities for assessments, linked to internal evaluation processes, to give within a training paradigm and anchored in the concept of negotiated quality, pointing to the development of the school, the teacher and student learning. Share analysis of research conducted in schools in the early years of elementary education at a municipal network. Data were collected through interviews and observations. We found that the ratings change pedagogical practices within schools presenting features neotechnicists, performative, and managerial control of the curriculum. In addition to our critical analysis, the research also focuses on purposeful looks.